2016
DOI: 10.1177/1947603515621997
|View full text |Cite
|
Sign up to set email alerts
|

The 50 Most Cited Articles in Orthopedic Cartilage Surgery

Abstract: Objective. To determine the 50 most cited articles in orthopedic cartilage surgery and their characteristics. Design. A systematic review of the Science Citation Index Expanded was performed for articles related to cartilage surgery published in the 66 journals under the category "Orthopedics." The 50 most cited articles were determined, and the following characteristics were analyzed for each article: authors, journal and year of publication, number of citations, geographic origin, article type (basic science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 36 publications
1
29
3
Order By: Relevance
“…However, the number of citations seems to be quite high when compared to the most cited articles in the subspecialty BOrthopaedic Cartilage Surgery^, for example, which may be a comparable Bhot topic^in the recent orthopaedic literature. The highest cited paper on this topic has reached 989 citations [19]. This is even more clear, when compared to highest cited papers in hand and shoulder surgery or paediatric orthopaedics [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the number of citations seems to be quite high when compared to the most cited articles in the subspecialty BOrthopaedic Cartilage Surgery^, for example, which may be a comparable Bhot topic^in the recent orthopaedic literature. The highest cited paper on this topic has reached 989 citations [19]. This is even more clear, when compared to highest cited papers in hand and shoulder surgery or paediatric orthopaedics [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 88%
“…Although a high number of total citations may not be the only parameter to determine the influence or clinical importance of an article, it can be considered as a parameter for the scientific relevance on a specialized subject [18][19][20]23]. Furthermore, such an analysis allows identifying the research activity in various fields.…”
Section: Discussionmentioning
confidence: 99%
“…The most common year of publication was 2009, and more than half of the included articles were published since 2010. This finding contrasts with other citation analysis studies in orthopaedics, which have found that older publications tend to have the greatest number of citations [24,27]. Although DAA hip arthroplasty has been used in clinical practice since the first half of the 20th century, this topic has just recently risen in prominence [9][10][11].…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, this research included 32.4% (12/37) level I and II studies. Many prior citation analyses have found that levels IV and V are most common and have found a much smaller percentage of level I and II studies among highly cited papers [17,18,20,22,24,27,31]. This is particularly interesting when considered in conjunction with the recency of the most highly cited papers.…”
Section: Discussionmentioning
confidence: 94%
“…In the recent years, some articles have been written on the most influential papers in the field of science in general 1 as well as various medical specialties, 2 3 4 5 6 7 8 9 10 11 12 13 including orthopedic surgery. 14 15 16 Besides these, various authors have attempted to find the most-cited papers in the different subspecialties of orthopaedics; 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 and also, influential papers from a particular region. 34 35 36 37 38 39 40 41 42 …”
Section: Introductionmentioning
confidence: 99%